Potentialities of using cryoprotectants in gluten-free frozen dough and microwave baking as an emerging technology (Research, Society and Development, 2021)
Disorders related to human health involving proteins that form the gluten network are increasingly in society, justifying the need to offer bakery products for this market niche. This study aimed to gather important information about the challenges involving technological production in the gluten-free bakery market. The approach encompasses the development of frozen dough for gluten-free baking, the use of cryoprotectants to maintain cell viability during the freeze-thawing step, the application of emulsifiers to improve the quality of the bread and the baking by an unconventional method using the microwaves. The introduction of frozen dough in the gluten-free bakery sector represents an interesting tool. However, these bread formulations require a higher amount of water compared to a traditional bread formulation (70 to 120 %), which makes the freezing and thawing steps extremely challenging, especially when it comes to the biopreservation of yeast cell viability. Cryopreservation with isolated and/or combined application of penetrating (glycerol) and non-penetrating (sucrose, fructo-oligosaccharide, trehalose, proteins and hydrocolloids) cryoprotectants promotes changes in the viscosity of the medium and is an excellent alternative for the maintenance of the microorganism responsible for the fermentation process. The appropriate choices of cryoprotectants, as well as the control of the freezing and thawing and baking processes, are important steps in the production line, to guarantee products with adequate technological and sensory qualities.